Amor Sustentable en las Comunidades de Aprendencia - Sanabria Jiménez, Mercedes (Universidad Santiago de Cali, 2020)
This articlewants to make visible how in autocratic educational communities, such as the school and the peniten-tiary, magical moments emerge where learners organize themselves in a harmonious dynamic of acceptance and interaction. The immersed research in the emerging paradigm allowed to unveil landscapes where sustanaible love becomes the mediator of learning builton selforganizing processes, conversational networks, collective networks, collectiveidentity, and interest in common learning. Sustanaible love ́s energy resides in the Akas-hic field, it permeates everythings that exists, in this sense it can gain certain spaces for learning to germinate, and the emergence of subtle acts that are woven synchronously with sustainable love for collective learning. Through the reflection that sprouted in recognition of magical moments, we identify minimum condi-tions, where the community of learning gestated, like: conversa-tional networks, individual and collective interactive relationships learning, identity and self-organization processes, accompanied by some basic principles that we call spores of respect, care, cooperation, sincerity, dialogue and listening, tickling for common learning, solidarity, trust, participation and joy, making the emergence of sustainable love visible for the transformation of educational communities into learning communities.